2016
DOI: 10.7314/apjcp.2016.17.4.1759
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Sarcoma: Clinical Presentation, Treatment and Survival Outcomes in Thailand

Abstract: Background: Uterine sarcoma is a group of rare gynecologic tumors with various natures, and different lines of treatment. Most have a poor treatment outcome. This study targeted clinical characteristics, treatment, overall survival (OS), progression-free survival (PFS), and prognostic factors in uterine sarcoma patients in one tertiary center for cancer care. Materials and Methods: Uterine sarcoma patients who were treated at the Department of Obstetrics and Gynecology, Faculty of Medicine Vajira Hospital betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 28 publications
8
21
1
Order By: Relevance
“…Histopathologic evaluations revealed that LMS and MMMT occurred in equal frequency in our group of patients (29.4%), followed by ESS (14.7%). Our data are comparable to some studies (7,16), but at the same time there are studies reporting very different histopathologic distributions in their results (17,18,19). It should be noted that small numbers of patients and changes in the WHO classification in each study may have caused these differences.…”
Section: Discussionsupporting
confidence: 91%
“…Histopathologic evaluations revealed that LMS and MMMT occurred in equal frequency in our group of patients (29.4%), followed by ESS (14.7%). Our data are comparable to some studies (7,16), but at the same time there are studies reporting very different histopathologic distributions in their results (17,18,19). It should be noted that small numbers of patients and changes in the WHO classification in each study may have caused these differences.…”
Section: Discussionsupporting
confidence: 91%
“…The mean ages of both groups were similar, as were the most common presenting symptoms. This is in agreement with the study by Putikul et al [7], which comprised 40 patients.…”
Section: Discussionsupporting
confidence: 94%
“…Stage I was the most common stage at presentation in both diseases. This is in agreement with the literature [7,9]. Comprehensive staging was performed for our CS patients with proven CS pathology in their preoperative biopsy, a policy that is in agreement with Venigalla et al [10], who performed a retrospective analysis of non-endometrioid types of endometrial carcinoma (7250 patients) with regard to the value of lymphadenectomy.…”
Section: Discussionsupporting
confidence: 85%
“…Despite intensive treatment, local recurrence and distant metastases are common. When a correct diagnosis is made preoperatively, surgical staging consisting of hysterectomy, salpingooopherectomy and lymph node resection is the mainstay of treatment (2). Addition of radiotherapy, chemotherapy, or hormonal therapy depends on the stage of the disease (3).…”
Section: Introductıonmentioning
confidence: 99%